Lung structure and function on MRI in preterm born school children with and without BPD: A feasibility study. Issue 12 (6th September 2022) - Elders, Bernadette B. L. J.; Tiddens, Harm A. W. M.; Pijnenburg, Mariëlle W. H.; Reiss, Irwin K. M.; Wielopolski, Piotr A.; Ciet, Pierluigi
Abstract: Background and Objective: The most common respiratory complication of prematurity is bronchopulmonary dysplasia (BPD), leading to structural lung changes and impaired respiratory outcomes. However, also preterm children without BPD may show similar adverse respiratory outcomes. There is a need for a safe imaging modality for preterm children with and without BPD for disease severity assessment and risk stratification. Our objective was to develop a magnetic resonance imaging (MRI) protocol in preterm children with and without BPD at school age. Methods: Nine healthy volunteers (median age 11.6 [range: 8.8–12.8] years), 11 preterm children with BPD (11.0 [7.2–15.6] years), and 9 without BPD (11.1 [10.7–12.6] years) underwent MRI. Images were scored on hypo‐ and hyperintense abnormalities, bronchopathy, and architectural distortion. MRI data were correlated to spirometry. Ventilation and perfusion defects were analyzed using Fourier Decomposition (FD) MRI. Results: On MRI, children with BPD had higher %diseased lung (9.1 (interquartile range [IQR] 5.9–11.6)%) compared to preterm children without BPD (3.4 (IQR 2.5–5.4)%, p  < 0.001) and healthy volunteers (0.4 (IQR 0.1–0.8)%, p  < 0.001). %Diseased lung correlated negatively with %predicted FEV1 ( r  = −0.40, p  = 0.04), FEV1 /FVC ( r  = −0.49, p  = 0.009) and FEF75 ( r  = −0.63, p  < 0.001). Ventilation and perfusion defects on FD sequence corresponded to hypointense regions on expiratory MRI. Conclusion: Chest MRI can identify structural and functional lung damage at school age in preterm children with and without BPD, showing a good correlation with spirometry. We propose MRI as a sensitive and safe imaging method (without ionizing radiation, contrast agents, or the use of anesthesia) for the long‐term follow‐up of preterm children.